Training on Financial Management and Preparation of Financial Reports for the Forest Farmers and Earth Mangrove Fishermen Group, Percut Village, Deli Serdang Regency - Bayu Wulandari; Munthe, Herlin; Namira Ufrida Rahmi; Maya Sabirina Panggabean; Jessi Charina Sembiring; Thomas Firdaus Hutahaean; Dianty Putri Purba; Ribka Sari Butar-Butar (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The method of implementing this service program will include financial management training and preparing financial reports. This training was held Thursday, September 26 2024. The address is Percut Village in Percut Sei Tuan sub-district, Deli Serdang Regency. The data collection techniques used are observation and community service methods, and the information is presented through lectures and discussions. Conclusions can be drawn from the results of the implementation of community service, including the following: a. Participants/Mothers of the Forest Farmers and Earth Mangrove Fishermen group, Percut Village, Deli Serdang Regency, have knowledge related to Financial Management and Financial Report Preparation material. B. Participants/residents of the Forest Farmers and Earth Mangrove Fishermen group, Percut Village, Deli Serdang Regency, have the ability to manage finances and prepare financial reports for future needs.